Personality, Organizational Culture, and Entrepreneurial Orientation on the Performance of Santripreneur - Wahyuni, Dewi Urip (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
Islamic boarding schools not only produce Islamic students but also begin to promote entrepreneurship to live independently and creatively in the community. This study aimed to determine the influence of personality, environmental culture, and entrepreneurial orientation on the performance of Santripreneur through entrepreneurial motivation in the Jombang Islamic Boarding Schools. This research was quantitative by using random sampling—the primary data by distributing questionnaires. The samples were 152 Santripreneurs—the method using SEM. The results confirmed all proposed hypotheses as well as the mediating effects. The finding confirms the role of enhanced-organizational culture in the Islamic setting in driving the creative business orientation of Santri in Indonesia.